Congenital anomalies in antenatal ultrasound scan at a tertiary care teaching hospital (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Early detection of congenital fetal anomalies by ultrasonography (USG) helps to identify the severity and termination of pregnancy in severe cases. Anomalies cause significant perinatal morbidity and mortality. Aim of this study was to analyse real-time USG detection of prenatal anomalies. Methods: This was a cross-sectional descriptive study of fetal anomalies detected during 2nd and 3rd trimester antenatal USG scan done from 2011 to 2015, in Patan Hospital. Age of mother, parity, gestational age when anomalies detected and, anomalies of previous child, use of folic acid were analysed. Descriptive analysis was done. Results: There were 35,571 deliveries in four years period with 134 (0.37%) congenital anomalies, 99 (79.2%) detected during antenatal USG during 2nd and 3rd trimester. Among 99 anomalies, 29 (29.29%) were detected before 22 weeks. Central nervous system (CNS) anomalies were 47, gastrointestinal 23, renal 12, skin and fetal compartment 8 and rest were less common. Young mothers of less than 30 years were 109 (81.34%) and primi were 85 (63.4%). Conclusions: Antenatal ultrasound can detect fetal anomalies in 2nd and 3rd trimester with higher frequencies belonging to the central nervous system followed by gastrointestinal tract anomalies and renal.